Sarkar, A. K. (2021). Tribes of the Sub-Himalayan region: Meches, Rabhas, Totos and Garos. New Delhi, India: Mittal Publications. ISBN 9788194936084. (195 pp.) - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies, 2026)
Tribes of Sub-Himalayan Region is a scholarly anthropological and sociological work that examines four indigenous communities of the Sub-Himalayan North Bengal region, the Meches, Rabhas, Totos, and Garos. Tracing their historical trajectories from antiquity to the early twenty-first century, the book offers a comprehensive analysis of their origins, belief systems, traditional customs, and socio-economic organization. Moving beyond descriptive ethnography, the author critically engages with the dynamics of cultural transformation, highlighting how colonial interventions, processes of modernization, and contemporary socio-economic pressures have profoundly influenced and reshaped the traditional life worlds of these tribal communities.
Keywords: New Delhi; Book Review